2022
DOI: 10.3389/fnmol.2022.827275
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Talks Among Bone Morphogenetic Protein (BMP) Signaling and Other Prominent Pathways Involved in Neural Differentiation

Abstract: The bone morphogenetic proteins (BMPs) are a group of potent morphogens which are critical for the patterning, development, and function of the central nervous system. The appropriate function of the BMP pathway depends on its interaction with other signaling pathways involved in neural differentiation, leading to synergistic or antagonistic effects and ultimately favorable biological outcomes. These opposite or cooperative effects are observed when BMP interacts with fibroblast growth factor (FGF), cytokines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 110 publications
(185 reference statements)
0
16
0
1
Order By: Relevance
“…Based on our results, BBC3 expression was decreased in tumor cells, which might be attributed to the reduced γ-radiation environment. It is also reported that Wnt6 and BMP2 are overexpressed in several malignancies ( 32 , 33 ). Conversely, their expression was decreased in FD-LSC-1 cells cultured in the DUGL, which suggested that Wnt6 and BMP2 might be involved in the growth repression caused by a low radiation environment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on our results, BBC3 expression was decreased in tumor cells, which might be attributed to the reduced γ-radiation environment. It is also reported that Wnt6 and BMP2 are overexpressed in several malignancies ( 32 , 33 ). Conversely, their expression was decreased in FD-LSC-1 cells cultured in the DUGL, which suggested that Wnt6 and BMP2 might be involved in the growth repression caused by a low radiation environment.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has confirmed that the activation of SMAD2/3 also participated in crosstalk with Hippo signaling when SMAD2/3 bound to the pathway transducer YAP, leading to cell growth regulation ( 42 ). Likewise, stimulating BMP2 can directly interact with the SMAD complex and subsequently promotes nuclear translocation to regulate target genes ( 33 ). The expression level of YAP trended upwards in contrast to cultures grown in parallel, although failed to reach statistical difference.…”
Section: Discussionmentioning
confidence: 99%
“…Ogn, with one of the highest transcript levels in NP over FAT cells, impacts proliferation and apoptosis in fibroblasts ( Deckx et al, 2016 ). Other transcripts with higher levels in NP over FAT but less studied in the context of the IVD ECM were Anos1 , encoding anosmin-1 associated with tumor progression ( Choy et al, 2014 ), and Bmper , encoding for a protein that inhibits Bmp signaling, therefore impacting many important signaling cascades critical in chondrogenesis ( Yoon and Lyons, 2004 ; Manzari-Tavakoli et al, 2022 ). Vwa5a transcripts encoding a tumor suppressor ( Zhou et al, 2009 ) were upregulated in FAT over NP cells.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is initiated by binding of the BMPs, a group of proteins of the TGF-β superfamily, to the heterodimeric Type I/Type II BMP transmembrane serine/threonine kinase receptors (Fig. 2 ) [ 26 ]. Then, either a Smad-dependent or a Smad-independent cascade is started intracellularly.…”
Section: Intracellular Signaling Pathways In Small Molecule-induced O...mentioning
confidence: 99%